El Salvador : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report, 2005)
This Report on the Observance of Standards and Codes on Fiscal Transparency on El Salvador reviews the fiscal transparency module. El Salvador needs to make progress on a number of important aspects of the code on fiscal transparency. It is also important to clarify the distribution of functions between levels of government, their roles in terms of expenditure and taxes, and to redefine the borrowing faculties of municipalities. The authorities could improve the transparency of the legal framework by introducing a legal requirement for all new regulations in the private sector.